What do Belarusians think about the EU and what can the EU do for Belarus?. Issue 1 (June 2014) - Melyantsou, Dzianis
This article focuses on Belarusians' attitudes towards integration, the EU and Russia, as well as on their motives for choosing foreign allies. To judge by its values, Belarusian society is closer to the Customs Union of Russia, Belarus and Kazakhstan than to the EU. Nevertheless, Belarusians' geopolitical preference is not the result of political or social values but is based on pragmatic calculations, according to which Europe successfully competes with Russia. Further growth of pro-European attitudes is limited by the frosty relations between Minsk and Brussels, difficulties with Schengen visas, and a general lack of knowledge about the EU.